PENGARUH PENDEKATAN RECIPROCAL TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 GUNUNG TULEH KABUPATEN PASAMAN BARAT TAHUN PELAJARAN 2012/2013 - Nelfia, Nelfia; Anggraini, Villia; Haryono, Yulia (STKIP PGRI Sumbar, 2013)
This research is based by the lack of understanding of the mathematical concepts that still low, reading comprehension of student with subject matter, textbook owned does not used properly, and student lest to practice or given opportunity for deliver about their understanding with reading topic. This research is aimed at knowing wheather the understanding of the mathematics concept of the students who are treated by used Reciprocal Teaching approach is better than understanding of the mathematics concepts of the students with conventional teaching. This type of research is experimental. The population of research is student class VIII SMPN 1 Gunung Tuleh West Pasaman 2012/2013 academic year that consist of 5 class. The technik data collection have done is random sampling, the class had choosen VIII4 for ekspriment class and class VIII3 for control class. Instrumen that used of post test with indicator concept understanding. Hypothesis test result that gotten P-value is 0,007<a, so it means that hypothesis is accepted, consequently it can be concluded that the understanding of the mathematics concept of the students who are treated by used Â Reciprocal Teaching approach is better than understanding of the mathematics concept of the students with conventional teaching class VIII SMPN 1 Gunung Tuleh Kabupaten West Pasaman.